Condições higiênico-sanitárias da estrutura dos boxes de alimentação em um centro comercial - ARAÚJO, Bianca Guimarães de Azevedo de (2023)
Eating out has become a habit among people who, for various reasons, need to be away from home for part of the day. Thus, the food tray on public roads is present in almost all places in the world, bringing practicality to those who need it and, consequently, constituting a source of income for many. Due to the risk inherent in hygienic practices for handling food, it is important that standards exist and are applied, both to assess and guide people involved in the handling and sale of food on public roads. This study aimed to evaluate the hygienic-sanitary conditions of food outlets in a shopping center in the city of Belém-PA. For this, a cross-sectional and descriptive observational study was carried out, using two checklists based on RDC's 216/2004 and 275/2002 (ANVISA). The study was carried out during the month of November 2022, with regular visits on Mondays, during the lunch hour. The results of the checklists applied include a total of 40 units, including: installation, floor, wall, ceiling, lighting, ventilation, water, sanitary facilities, integrated vector and urban pest control, waste management, equipment, equipment and furniture. Among them, 3 units (7.5%) were compliant (C); 28 units (70%) as Non-Compliant (NC) and 9 units (22.5%) as Not Applicable (NA). Thus, a lack of technical knowledge of good food handling practices was verified through the application of checklists in the places where meals are sold, portrayed by non-compliance with most standards.